Water management and irrigation for bulb onion (Allium cepa L.) growth and development in the Papua New Guinea Highlands - Aku, Rodney; Kristiansen, Paul; Coleman, Michael (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2023)
Water is crucial for nutrient intake, transportation, temperature regulation, and photosynthesis in bulb onion (Allium cepa L.) growth and development. Water scarcity, caused by climate variability and particularly during prolonged dry periods, has proved to be an obstacle to cultivating bulb onions in the Papua New Guinea (PNG) Highlands. Farmers have a limited grasp of the interdependence of soil, water, and plants. They have traditionally depended on precipitation, and water from streams and rivers, to irrigate their bulb onion crops. The main method for providing irrigation support is manual irrigation, with agricultural organisations assisting with basic irrigation technologies. Despite farmers and organisations efforts to improve irrigation practices, the prolonged dry season still raises labour demands for bulb onion farms. Farmers’ lack of knowledge about irrigation technology and soil water conservation contributes to this issue. Moreover, the lack of irrigation suppliers worsens the issue of limited soil water in onion farms. This paper gives an overview of onion production in PNG, focusing on irrigation practices and constraints in the Highlands region. It aims to stress irrigation’s importance in crop growth and explore PNG’s irrigation methods and soil moisture conservation practices. There is a need for a sustainable irrigation and soil water conservation system that is easy to use and incorporates crop water requirements. This system is vital for watering onions and conserving soil moisture, promoting their growth and yield. In this context, the use of mulch and irrigation systems can preserve and enhance soil moisture during prolonged dry phases.